Was there a “Bedouinization of Arabia”? - Macdonald, M (De Gruyter, 2015)
In 1953, Werner Caskel produced a theory which he called “the Bedouinization of Arabia”. In this, he maintained that around AD 100 Arabia was peaceful, dominated by settled states, with some non-tribal nomads who were simply “shepherds near the cities”. He contrasted this with Arabia in the sixth and seventh centuries in which he claimed “the Bedouin form of society and ideo logy prevailed”. The evidence he provided for this false dichotomy consisted of errors, misunderstandings and argumenta ex silentio, as was pointed out at the time, but his theory has nevertheless been widely accepted in the years which followed. In 1959, it was taken up and adapted by Walter Dostal who tried to explain the “Bedouinization” by producing a novel definition of the Bedouin as “camel-herders accustomed to fighting as rider warriors” and said that “Vollbeduinen” were only those who used the shadād or so-called “North-Arabian” camel saddle which, he imagined, gave them a secure seat from which to fight. In fact, however, there is no evidence at all that nomads in Arabia have ever fought from camel-back if they could possibly get off to fight on foot or on horseback. Nevertheless, in 1975, Richard Bulliet adopted Dostal’s idea and took it further by claiming that the use of the shadād made camel-riders an almost invincible force and this produced “an alteration in the balance of political power in favour of the nomads”. This gave apparent support to Caskel’s idea that the North Arabian Bedouin were able to sweep to military and political domination of the sedentaries by the sixth century AD. The present examination of these theories shows that there is no basis to them and, in doing so, argues that what is known of nomadic life in Arabia between AD 100 and 500 suggests continuity both in its structures and in its relations with the sedentaries.